Study and application of optical properties for nondestructive interior quality inspection of fruit - YING Yi-bin; LIU Yan-de (浙江大学学报. 农业与生命科学版)
Nondestructive quality inspection and sorting technique based on fruit optical properties is widely used in post-harvest processing and quality control. The fruit interior quality inspecting systems and their detecting principle were introduced. Three different kinds of measuring methods, such as regular reflection, diffuse reflection and transmittance, were analyzed. The studies and their advancements related to inspection of sugar content, acidity and firmness of fruits, were reviewed. Finally, the application prospects of this technology were formulated.